Joint effect of paid working hours and multiple job holding on work absence due to health problems among basic education teachers in Brazil: the Educatel Study - Lucía Rodríguez-Loureiro; Lucía Artazcoz; María López-Ruiz; Ada Ávila Assunção; Fernando G. Benavides (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: The objectives were to assess the joint effect of working hours paid per week and multiple job holding on sickness absence, by sex, among basic education teachers in Brazil. This study is based on a survey carried out over a representative sample of 5,116 active basic education teachers in Brazil between 2015 and 2016 (Educatel Study). We created a dummy variable to assess the joint effect of weekly paid working hours [standard (35-40 hours); part-time (< 35 hours); moderately long (41-50 hours); and very long (> 50 hours)] and multiple job holding (working in several schools - no/yes). Working 35-40 hours in one school was the reference category. We conducted Poisson regression models with robust variance to obtain prevalence ratios (PR) and 95% confidence intervals (95%CI) of the association with self-certified sickness absence and medically certified sickness absence. Models were adjusted for age, type of contract and salary, and stratified by sex. Significant associations with sickness absence were only found among teachers working in more than one school. Associations with self-certified sickness absence were found among women with standard and men with moderately long working hours, and for both women and men working > 50 hours (PR: 1.21, 95%CI: 1.09-1.35; PR: 1.40, 95%CI: 1.18-1.66; respectively). Associations with medically certified sickness absence were found among teachers working > 50 hours, among women (PR: 1.30, 95%CI: 1.03-1.63) and men (PR: 1.41, 95%CI: 1.04-1.92). Teachers working longer hours in several schools could be suffering health problems, deriving in work absence.